Spatial Effects in Willingness to Pay for Avoiding Nuclear Risks - Yves Schneider; Peter Zweifel (Swiss Journal of Economics and Statistics, 2013)
How to deal with the risks associated with nuclear energy is a major policy issue. This paper investigates the effect of an individual's distance from nuclear power plants on its willingness to pay for increased insurance coverage against nuclear accidents (MWPC) as well as on willingness to pay for solving the nuclear waste disposal problem (MWPW). Using data from a discrete choice experiment conducted in Switzerland, we find evidence that MWPC values decrease with distance from plant once attitudes influencing choice of residential location are controlled for. However, distance from plant has no effect on MWPW values.
Keywords: R3; L94; C9; 330; discrete choice experiment; liability insurance; nuclear accident; willingness to pay